Evaluation of Aligners from the perspective of an Orthodontist and General Dentist - Gupta, Sweety; Tikku, Tripti; Verma, Sneh Lata; Khanna, Rohit; Srivastava, Kamna (Orthodontic Journal of Nepal, 2024)
Background: Aligners are a relatively new technique in dentistry for achieving tooth alignment. While their aesthetic appeal is undeniable, the perception among orthodontists and general dentist needs to be evaluated. Aims and Objectives: This study aimed to evaluate the perception of orthodontic aligners among general dentists and orthodontists in India. Materials and Method: A cross-sectional survey including 200 practicing general dentists and orthodontists was carried out using a web-based questionnaire (17 questions for orthodontists, 14 for dentists) was developed and distributed through social media platforms. The questionnaire addressed use of aligner, digital workflow, case selection, challenges encountered, treatment outcomes, and views on in-home digital scanning. Responses were tabulated and analyzed as percentages. Result: Overall, 66.3% of practicing orthodontists and 82.6% of general dentists have aligner treatment facility in their clinic out of which 19.5 % of general dentist practice aligners on their own. Reluctance to use aligners stemmed from perceived high cost, patient compliance concerns, unpredictable results, and lack of training. Most treated cases were mild, non-extraction discrepancies. Interestingly, over 50% of general dentists supported the concept of in-home digital scanning. 75% of orthodontists acknowledged the need to switch to alternative orthodontic appliances and use of auxiliaries to achieve desired outcomes. Conclusion: Not only orthodontists but majority of general dentists were also aware of aligners and are practicing it, stressing on its increased use as treatment modality for correcting orthodontic cases with discrepancies not necessitating teeth extraction in adult subjects.